2017
DOI: 10.15376/biores.12.1.1706-1722
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization for Citrus Waste Biorefinery via Simultaneous Pectin Extraction and Pretreatment

Abstract: In a novel valorization approach for simultaneous pectin extraction and pretreatment (SPEP) of citrus waste (CW) by dilute nitric acid and ethanol, almost all of the CW was converted to bio-derived chemicals in a singlestep process at a low/moderate temperature. The SPEP was performed at different temperatures (70 °C and 80 °C), pH (1.8, 3.0, and 4.3), and extraction times (2 h and 3 h) with a full factorial design. The maximum pectin yield of 45.5% was obtained at pH 1.8, 80 °C, and 2 h. The pectin yields at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The percentage is more than 4% if one deals with the dried citrus waste [110]. Current research has shown a new technical process that increases the pectin yield from~40% of wet citrus waste to 58% [111]. The return from pastazzo in bran production for animal feed is more than it is for pectin production [110].…”
Section: Status-quo Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage is more than 4% if one deals with the dried citrus waste [110]. Current research has shown a new technical process that increases the pectin yield from~40% of wet citrus waste to 58% [111]. The return from pastazzo in bran production for animal feed is more than it is for pectin production [110].…”
Section: Status-quo Analysismentioning
confidence: 99%
“…Pectin production from citrus waste is a relatively new route. During the past decade, several studies have investigated technology innovations to optimize the pectin yield [111,113]. The innovative process and the low return from pectin production could represent a huge barrier, even if there is a large demand for pectin in the market [82].…”
Section: Status-quo Analysismentioning
confidence: 99%
“…The composition of total carbohydrates was similar in both sludges, while all other compounds were different. Activated sludge as well as other organic wastes "contain soluble sugars (mainly fructose, glucose, and sucrose), structural polysaccharides (cellulose, hemicelluloses, and pectin), lignin-like compounds (flavonoids), and essential oils" [42].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage is more than 4% if one deals with the dried citrus waste (Rezzadori et al, 2012). Current research has shown a new technical process that increases the pectin yield from ~40% of wet citrus waste to 58% (Satari et al, 2017). The return from pastazzo in bran production for animal feed is more than it is for pectin production (Rezzadori et al, 2012).…”
Section: Status-quo Analysismentioning
confidence: 99%
“…Pectin production from citrus waste is a relatively new route. During the past decade several studies have investigated technology innovations to optimize the pectin yield (Kim et al, 2004;Satari et al, 2017). The innovative process and the low return from pectin production could represent a huge barrier even if there is a large demand for pectin in the market (Bae et al, 2016).…”
Section: Status-quo Analysismentioning
confidence: 99%